Association between fat‐infiltrated axillary lymph nodes on screening mammography and cardiometabolic disease. (3rd May 2022) - Song, Qingyuan; diFlorio‐Alexander, Roberta M.; Patel, Sohum D.; Sieberg, Ryan T.; Margron, Michael J.; Ansari, Saif M.; Karagas, Margaret R.; Mackenzie, Todd A.; Hassanpour, Saeed
Abstract: Objective: Ectopic fat deposition within and around organs is a stronger predictor of cardiometabolic disease status than body mass index (BMI). Fat deposition within the lymphatic system is poorly understood. This study examined the association between the prevalence of cardiometabolic disease and ectopic fat deposition within axillary lymph nodes (LNs) visualized on screening mammograms. Methods: A cross‐sectional study was conducted on 834 women presenting for full‐field digital screening mammography. The status of fat‐infiltrated LNs was assessed based on the size and morphology of axillary LNs from screening mammograms. The prevalence of cardiometabolic disease was retrieved from the electronic medical records, including type 2 diabetes mellitus (T2DM), hypertension, dyslipidemia, high blood glucose, cardiovascular disease, stroke, and non‐alcoholic fatty liver disease. Results: Fat‐infiltrated axillary LNs were associated with a high prevalence of T2DM among all women (adjusted odds ratio: 3.92, 95% CI: [2.40, 6.60], p ‐value < 0.001) and in subgroups of women with and without obesity. Utilizing the status of fatty LNs improved the classification of T2DM status in addition to age and BMI (1.4% improvement in the area under the receiver operating characteristic curve). Conclusion: Fat‐infiltrated axillary LNs visualized on screening mammograms were associated with the prevalence of T2DM. If further validated, fat‐infiltrated axillary LNs may represent a novel imaging biomarker of T2DM in women undergoing screening mammography.